Case report and literature analysis: solitary HCC- recurrence in the right maxillary sinus after curative resection - Madzikatire, Tinotenda Blessing; Shan, Yunfeng (Frontiers in Oncology, 2024)
Background The primary treatment for eligible patients with hepatocellular carcinoma (HCC) is curative liver resection, offering a 5-year overall survival (OS) of 60%-80%. Despite this, the recurrence rate within five years post-resection remains notably high, ranging from 40% to 50%. Instances of recurrence in the maxillary sinus following liver resection are exceedingly uncommon. This report details a unique case of solitary maxillary sinus recurrence after the curative resection of HCC, which underwent maxillary tumor resection, along with a comprehensive review of pertinent literature. No similar cases have been documented previously. Case presentation In 2014, an 85-year-old male patient was diagnosed with HCC and subsequently underwent left hepatectomy. Following the resection, the patient underwent a 9-year follow-up period without any evidence of intra or extrahepatic recurrence. In 2023, a computed tomography (CT) scan revealed a 1.4 cm by 1.1 cm mass in the maxillary sinus, without discernible invasion of the alveolar sinus, nasal cavity, orbital cavity, or infratemporal space. We proceeded with the resection of the maxillary sinus mass. Patho-histochemical analysis indicated that the tumor cells in the maxillary sinus were metastatic HCC cells. As of now, the patient remains in good condition with no signs of tumor recurrence. Conclusion For patients presenting with solitary maxillary sinus metastasis, optimal liver function, and a favorable performance score, tumor resection may be the preferred treatment option. However, given the rarity of such cases, larger prospective trials are essential to determine an optimal treatment strategy that offers therapeutic benefits.